Craft beer: cultura, identidade e tendências de consumo na cidade do Recife. - Tschá, Anna Regina (2018)
In recent years, there has been a change in the country's brewing sector with the entry of imported products, as well as inputs and the adhesion of the technique of producing artisanal beers, at significant scales. What used to be considered as a hobby with home-made products, has gained space and microbrewery, which now occupy a significant portion of the market, has emerged. In addition to investment in research and development for the production of malt and local yeasts. Just as there was a transformation in the production sector, there was also a change in the profile of the consumer, who became more demanding, attentive to their rights, and began to seek constant experiences. The choice of this theme was due to the restlessness in identifying the cultural change that began in the middle of the year of 2015 in the city of Recife. Seeking to investigate the tendency of the consumer profile, besides the social and cultural aspects that involve the tasting of artisanal beers in the city of Recife, capital of the State of Pernambuco. Thus, we opted for a focus on the phenomenological-hermeneutic method for carrying out the research methodology, which was quantitative. The research findings pointed to a consumer who does not tend to be loyal to brands, because among their characteristics the exploratory profile prevails. He is willing to pay more to drink a beer with superior technical qualities, which stimulate his somatosensory senses and seek constant innovations in the products. It was also observed through the consonance of academic research with market research, the power of drink as an instrument of interaction, social differentiation and cultural identity.